Efficient and Direct Route to 5-Iodo-4H-Quinoxalines via Copper-Catalyzed Double C–N Arylations of 1,2,3-Triiodoarenes: Potential Application towards 5-Substituted 4H-Quinoxalines - Al-Zoubi, Raed M.; Al-Jammal, Walid K.; Shkoor, Mohanad; Bani-Yaseen, Abdulilah D.; Ferguson, Michael J. (Synthesis, 2024)
A simple, direct, and regioselective protocol to substituted 5-iodo-4H-quinoxalines through double C–N arylations of 1,2,3-triiodobenzenes and 1,2-diamines is reported. Remarkably, the N-arylation couplings proceed unimolecularly at the vicinal positions, the most active and less hindered positions. This process tolerates a wide range of aromatic substrates. The reactions of electron-deficient 1,2,3-triiodoarene systems and DMEDA under the optimized conditions provided the highest isolated yields. The chemical transformation of the target compound, which serves as a valuable precursor in synthesis, was successfully demonstrated in the Suzuki–Miyaura reaction, giving the desired coupling derivatives with excellent isolated yields. This article describes a method for the first and unprecedented synthesis of 5-iodo-4H-quinoxalines that is regioselective, scalable, and provides useful derivatives for other chemical reactions
Keywords: quinoxalines; C–N arylation; iodination; catalysis; Ullmann-type coupling